ON SOME AUTOMORPHISMS IN AFFINE SPACES - Hadžieva, Elena; Kocić, Ljubiša (Matematichki Bilten, 2011)
This paper deals with the affine mappings defined on affine space, especially on the real affine space \(A^m\). Their matrix representation in the form of real column-stochastic matrix is given. We show that every linear mapping defined on \(\mathbb{R}^m\) can be observed as an affine mapping defined on \(A^m\). We also show an important property - a special commutativity of the composition of two affine mappings.
Keywords: affine space; affine basis; affine mapping; matrix representation; commutativity